Scalloped tongue is associated with nocturnal intermittent hypoxia among community‐dwelling Japanese: the Toon Health Study. (16th June 2017) - Tomooka, K.; Tanigawa, T.; Sakurai, S.; Maruyama, K.; Eguchi, E.; Nishioka, S.; Miyoshi, N.; Kakuto, H.; Shimizu, G.; Yamaoka, D.; Saito, I.
Summary: Scalloped tongue is considered as a possible clinical finding of obstructive sleep apnoea (OSA). There are few evidence of the association between scalloped tongue and OSA. To examine the association between scalloped tongue and nocturnal intermittent hypoxia (NIH), a surrogate marker of OSA, among a general Japanese population. Study participants were 398 men and 732 women aged 30–79 years who participated in the Toon Health Study from 2011 to 2014. Scalloped tongue was classified into three categories: none, mild and moderate‐to‐severe. Moderate‐to‐severe NIH was defined as the 3% oxygen desaturation index of ≥15 events/h during sleep for one night with pulse oximetry. The multivariable‐adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for moderate‐to‐severe NIH were calculated according to scalloped tongue categories using a logistic regression model. There were 69 (6·1%) moderate‐to‐severe NIH cases in this population. The multivariable‐adjusted ORs (95% CIs) of moderate‐to‐severe NIH were 1·59 (0·85–2·95) for mild and 2·39 (1·10–5·17) for the moderate‐to‐severe scalloped tongue group compared with the group without scalloped tongues. When stratified by overweight status (BMI <25 or ≥25 kg m −2 ), the respective ORs (95% CIs) were 2·83 (1·06–7·55) and 4·74 (1·28–17·49) among overweight individuals, and 0·94 (0·40–2·70) and 1·52 (0·57–4·05) among non‐overweight individuals. Scalloped tongue was associated with higher prevalence of moderate‐to‐severe NIH among the general Japanese population and this association was more evident in overweight individuals.